Analisis SWOT Ketercapaian Tujuan Dibentuknya KOSP Berdasarkan Kurikulum Merdeka Belajar di SMP Swasta IT Ad Durrah Marelan - Siti Fatimah Azzahro Simatupang (Universitas Negeri Malang, 2025)
Abstract: The purpose of this study is to describe the achievement of the formation of KOSP by using SWOT analysis, knowing the role of leadership in overcoming the difficulties of teachers, students and parents regarding the independent curriculum program. The method used is a qualitative research method. With the approach of library research, which is a research method that analyzes a topic from a collection of data found from various literatures and is carried out at the Private Junior High School of IT Ad Durrah Marelan. The data analysis used consisted of data reduction, data presentation, and conclusion drawn. The results of the Swot Analysis research on the achievement in the form of Kosp include strengths: the ability of teachers who are still of productive age, socio-cultural community and community support. Opportunities: It Ad durrah Junior High School has become a driving school, there are not many IT schools that focus on the implementation of the independent curriculum and life skills of students. Weakness: changing the mindset of teachers who are still static to dynamic, making parents' understanding of learning does not have to be in the classroom, budget and infrastructure. Threats: The transition process that is still a lot makes parents and the community less accepting that teaching does not have to be in the classroom. For the achievement of the goal of forming the Kosp, it can be seen from the student learning report card, the P5 report card, and the school education report card Keywords: SWOT Analysis; KOSP;Independent Curriculum Abstrak: Tujuan dari penelitian ini yaitu guna mendeskripsikan Ketercapaian dibentuknya KOSP dengan cara menggunakan analisis SWOT , Mengetahui peran kepemimpinan dalam mengatasi kesulitan guru, siswa dan orang tua mengenai program kurikulum merdeka. metode yang digunakan adalah metode penelitian kualitatif. Dengan pendekatan studi Pustaka (library research), yaitu metode penelitian yang menganalisa suatu topik dari kumpulan data yang ditemukan dari berbagai literatur dan dilaksanakan di Smp Swasta It Ad Durrah Marelan. Adapun analisis data yang digunakan terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian Analisis Swot ketercapaian di bentuk nya Kosp diantaranya strengths: kemampuan guru yang masih berusia produktif, sosio kultur masyarakat dan dukungan masyarat. Opportunities: Smp It Ad durrah sudah menjadi sekolah penggerak, tidak banyak sekolah it yang fokus implementasi kurikulum merdeka dan life skill peserta didik. Weakness: mengubah mindset guru yang masih statis menjadi dinamis, membuat pemahaman orang tua belajar tidak harus dikelas, anggaran dan sarana prasaran. threats: Proses transisi yang masih banyak membuat pemhaman orang tua dan masyarakat kurang menerima bahwa bekajar tidak harus di dalam kelas. Untuk ketercapaian tujuan dibentuk nya Kosp dapat dilihat dari rapot hasil belajar siswa, Raport P5, dan Raport pendidikan sekolah. Kata kunci: Analisis SWOT; KOSP; Kurikulum Merdeka